The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/dairy3020023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exogenous Fibrolytic Enzyme Derived from Trichoderma reesei on Rumen Degradation Characteristics and Degradability of Low-Tannin Whole Plant Faba Bean Silage in Dairy Cows

Abstract: The objectives of this study were to (1) determine the effect of exogenous fibrolytic enzyme derived from Trichoderma reesei on dry matter (DM) and neutral detergent fibre (NDF) degradability of whole plant faba bean silage (Snowbird), (2) evaluate the effects of fibrolytic enzyme (FETR) on DM and NDF degradation kinetics of whole plant faba bean silage, and (3) compare the difference between in the vitro approach (DaisyII incubation method) and the in situ assay-biological approach (nylon bag technique) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…May be the presence of exogenous enzymes (cellulase + xylanase + alfa amylase + protease) in Zad group enhanced and increased the soluble fraction (a). The same effect was noted by Yang et al, (2022) on whole plant faba bean silage that treated with gradually levels of exogenous fibrolytic enzyme derived from Trichoderma reesei with concentrations from zero to 1.5 (ml/Kg) that resulted in increasing soluble fraction of DM from 25.10 to 29.24%, respectively. Using exogenous fibrolytic enzymes resulted in pre-digestion effect that increased the soluble fraction of DM (Pinos-Rodrıguez et al, 2008).…”
Section: In Vitro Degradability Characteristicssupporting
confidence: 71%
“…May be the presence of exogenous enzymes (cellulase + xylanase + alfa amylase + protease) in Zad group enhanced and increased the soluble fraction (a). The same effect was noted by Yang et al, (2022) on whole plant faba bean silage that treated with gradually levels of exogenous fibrolytic enzyme derived from Trichoderma reesei with concentrations from zero to 1.5 (ml/Kg) that resulted in increasing soluble fraction of DM from 25.10 to 29.24%, respectively. Using exogenous fibrolytic enzymes resulted in pre-digestion effect that increased the soluble fraction of DM (Pinos-Rodrıguez et al, 2008).…”
Section: In Vitro Degradability Characteristicssupporting
confidence: 71%
“…Treating AMF with exogenous enzyme might improve their utilization by dairy cows as it has been previously shown that exogenous fibrolytic enzyme increase milk parameters ( Gado et al., 2009 ; Golder et al., 2019 ). Fibrolytic enzymes enhance DM digestibility ( Yang et al., 2022 ) by increasing DM, OM and CP, and decreasing NDF and ADL ( Kumar et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Giraldo et al [29] observed enhanced fibrolytic activity in ruminal fluid when sheep were administered EFE @ 12 g/d intra-ruminally. These variable responses by fibrolytic enzymes across experiments may be due to differences in the enzyme's activity,substrate specificity, internal rumen environment and mode of application [30].…”
Section: Methods Of Application Of Enzymesmentioning
confidence: 99%